Effects of a Hybrid Education Programme for Korean Mothers of Children with Atopic Dermatitis - Je-Bog Yoo; Jennie C. De Gagne; Seung-Hyeon S. Jeong; Chan-Woo Jeong (Medical Journals Sweden, 2017)
Atopic dermatitis (AD), a common childhood skin disorder, can limit a child's learning and physical activities. South Korean mothers, as primary caregivers, experience anxiety and helplessness when caring for their ill children. The aim of this study was to develop a hybrid AD education programme (consisting of a face-to-face session followed by 8 online sessions) and evaluate its effects on anxiety, caregiving efficacy and caregiving behaviour among mothers of children with AD. Twenty mothers of patients with AD treated in a South Korean hospital received one on-site session and 8 weekly online modules. After the intervention, mothers' mean±standard deviation anxiety reduced (from 50.3 ± 14.2 to 31.7 ± 6.3 points, t = 5.75, p <0.001). Their caregiving efficacy and caregiving behaviour improved significantly, from 18.3 ± 3.5 to 29.4 ± 3.2 points (t = -9.64, p< 0.001) and from 47.7 ± 7.7 to 78.8 ± 4.9 points (t = -14.4, p <0.001), respectively. The effects of the hybrid education programme for this population were significant. Healthcare providers should consider examining the programme nationwide, including in rural areas, while investigating its long-term effects.